2020
DOI: 10.1126/scitranslmed.aay3850
|View full text |Cite
|
Sign up to set email alerts
|

A high-salt diet compromises antibacterial neutrophil responses through hormonal perturbation

Abstract: The Western diet is rich in salt, which poses various health risks. A high-salt diet (HSD) can stimulate immunity through the nuclear factor of activated T cells 5 (Nfat5)–signaling pathway, especially in the skin, where sodium is stored. The kidney medulla also accumulates sodium to build an osmotic gradient for water conservation. Here, we studied the effect of an HSD on the immune defense against uropathogenic E. coli–induced pyelonephritis, the most common kidney infection. Unexpectedly, pyelonephritis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 50 publications
2
66
1
Order By: Relevance
“…In conjunction with evidence that environmental factors such as diet or other industrial food additives (i.e., salt [63,64]), as well a proinflammatory gut environment can lead to an increased intestinal permeability [65] and susceptibility to invasive pathobionts [66], and that inflammation per se can shift gut microbial composition [67], it is currently unclear whether inflammation is at the dispensing/receiving or both ends of gut microbiome shifts culminating in increased bacterial translocation.…”
Section: Dietary Signals In the Crosstalk Between Gut Microbiome And mentioning
confidence: 99%
“…In conjunction with evidence that environmental factors such as diet or other industrial food additives (i.e., salt [63,64]), as well a proinflammatory gut environment can lead to an increased intestinal permeability [65] and susceptibility to invasive pathobionts [66], and that inflammation per se can shift gut microbial composition [67], it is currently unclear whether inflammation is at the dispensing/receiving or both ends of gut microbiome shifts culminating in increased bacterial translocation.…”
Section: Dietary Signals In the Crosstalk Between Gut Microbiome And mentioning
confidence: 99%
“…To identify the mechanisms behind these changes, we focused our investigations on circulating components with the potential to alter BBB. Highsalt intake is known to induce changes in mineralocorticoid and glucocorticoid levels in both mice and humans (15)(16)(17)(18). We detected elevated levels of corticosterone in the serum of HSD-fed OSE mice (Fig.…”
Section: Na Et Almentioning
confidence: 64%
“…In ischemic tissues, neutrophils catabolize Gln as a carbon source for free radical and cytokine production via anaplerotic shunting of Gln to the Krebs cycle (Cruzat, Macedo Rogero, Noel Keane, Curi, & Newsholme, 2018; Metallo et al., 2011; Newsholme et al., 1999; Wang et al., 2019). In a recent study investigating the impact of a high‐salt diet on susceptibility pyelonephritis, Jobin et al reported that glucocorticoid‐mediated suppression of neutrophil function exacerbates pyelonephritis in mice (Jobin et al., 2020). Elevated corticosterone levels in acidotic rodents has been reported (May, Kelly, & Mitch, 1986) and therefore stimulation of glucocorticoid production by metabolic acidosis may represent an alternative mechanism for increased susceptibility to pyelonephritis.…”
Section: Discussionmentioning
confidence: 99%